Visual Asset Characters Design for Webcomic “If I were you, Mom!” - Cennywati, Cennywati (Universitas Ciputra, 2026)
The increasing demand for high-frequency webcomic production presents a challenge in maintaining visual consistency while ensuring production efficiency, particularly in four-panel (4-koma) formats that require clarity and repetition. In this context, character design plays a crucial role in conveying personality, emotion, and narrative function effectively within limited visual space. This study explores the design of the main characters in the webcomic If I Were You, Mom! which portrays everyday family life intertwined with conflicts arising from a body-swapping incident between a grocery store owner and her middle school daughter. This study aims to develop and implement a structured minimalist character design process that supports production efficiency while maintaining strong visual identity, as well as to validate its effectiveness through audience perception. This study is using a descriptive qualitative method, using visual reference analysis, sketch exploration, character sheet development, and audience-based visual validation through questionnaires. The evaluation’s result was an overall mean score of 4.09 (good category), indicating that the character designs convey effectively identity, role suitability, and emotional expression, therefore showing the viability of a minimalist visual strategy for serialized webcomic production.